(untitled) (Andamios, Revista de Investigación Social, 2007)
Among the third generation of human rights, the appeal for a diachronic solidarity between the human community and the extrahuman natural world, and for a synchronstic one between the community of living human beings and hypothetical members of future human generations, has a significant place. This paper analyzes from a critical perspective the reasons for and against this proposal of duties and intergenerational ethical obligations in the context of a techno-scientific civilization, with the aim of grounding the current generation´s responsibility regarding the elaboration of a global ethics that could face the demands of future generations.